An optimized set of human telomere clones for studying telomere integrity and architecture - Knight, S; Lese, C; Precht, K; Kuc, J; Ning, Y; Lucas, S; Regan, R; Brenan, M; Nicod, A; Lawrie, N; Cardy, D; Nguyen, H; et al. (University of Chicago Press, 2000)
Telomere-specific clones are a valuable resource for the characterization of chromosomal rearrangements. We previously reported a first-generation set of human telomere probes consisting of 34 genomic clones, which were a known distance from the end of the chromosome (~300 kb), and 7 clones corresponding to the most distal markers on the integrated genetic/physical map (1p, 5p, 6p, 9p, 12p, 15q, and 20q). Subsequently, this resource has been optimized and completed: the size of the genomic clones has been expanded to a target size of 100-200 kb, which is optimal for use in genome-scanning methodologies, and additional probes for the remaining seven telomeres have been identified. For each clone we give an associated mapped sequence-tagged site and provide distances from the telomere estimated using a combination of fiberFISH, interphase FISH, sequence analysis, and radiation-hybrid mapping. This updated set of telomeric clones is an invaluable resource for clinical diagnosis and represents an important contribution to genetic and physical mapping efforts aimed at telomeric regions.